Determinants of Tax Morale in Former Yugoslavian Countries. Issue 2 (3rd March 2020) - Crnogorac, Marko; Lago-Peñas, Santiago
ABSTRACT: In this paper, we perform an empirical analysis on the determinants of tax morale in former Yugoslavian countries, including both individuals' attributes and contextual variables. We use survey data from the 2008 European Values Study as well as fiscal and economic macro-data. Our results reveal that the outcomes for individual-level variables are in line with the previous scientific literature. Moreover, the results on contextual variables and the interactions associated with tax burden and economic freedom provide new insights concerning tax morale in these countries.